Yiddish Given Names A Lexicon - Cohn, Rella Israly (Lanham : Scarecrow Press, 2008)
This is a lexicon of Yiddish given names, preceded by four chapters of material that explains the lexical conventions, the historical environment, and the research applicable to this subject.
Description based upon print version of record.
Keywords: Names, Personal -- Jewish; Names, Personal -- Yiddish; Yiddish language -- Etymology -- Names; Names, Personal -- Yiddish; Names, Personal -- Jewish; Yiddish language -- Etymology -- Names; REFERENCE / Genealogy & Heraldry; Electronic books